Notarial Prevention Safeguards Mortgage Right Loan Agreements in Indonesia: Pencegahan Notarial Melindungi Perjanjian Pinjaman Berbasis Hak Tanggungan di Indonesia - Pradana, Nanda Gita Putri; Rahayu, Mella Ismelina Farma (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Loan agreements secured by land certificates remain highly vulnerable to civil disputes in Indonesia, particularly when executed without authentic deeds and registered mortgage rights. Specific Background: The dispute examined in Wonosari District Court Decision Number 44/Pdt.G/2021/PN Wno involved a loan agreement valued at IDR 1,750,000,000 secured by eight Certificates of Ownership and formalized solely through an underhand deed without notarial involvement or Mortgage Right registration. Knowledge Gap: Previous discussions on Indonesian contract law have insufficiently emphasized the preventive legal function of Notaries in protecting creditors through authentic deeds and executory guarantees in high-value financial transactions. Aims: This study analyzes the validity of underhand loan agreements, the application of the good faith principle, and the legal consequences arising from the absence of the Notary’s preventive function and unregistered mortgage rights. Results: The findings demonstrate that the agreement remained legally valid under Article 1320 of the Civil Code; however, the absence of an authentic deed substantially weakened the creditor’s evidentiary position and eliminated executory rights over the collateral. The court applied the principle of good faith to establish debtor default but reduced the creditor’s claimed interest from IDR 1.28 billion to IDR 58.6 million and rejected the penalty claim. Novelty: This study highlights the cumulative legal losses caused by the absence of preventive notarial protection in mortgage-based lending transactions. Implications: The findings underline the necessity of authentic deeds, registered mortgage rights, and preventive notarial supervision to strengthen legal certainty and creditor protection in Indonesian financial agreements. Highlights: Unregistered collateral eliminated executory rights over eight land ownership certificates. Good faith doctrine supported judicial recognition of debtor default in civil litigation. Interest recovery was drastically reduced because contractual evidence lacked formal authentication. Keywords: Notary's Preventive Function, Loan Agreement, Underhand Deed, Good Faith, Mortgage Right.